Evidence of in utero infection by Mycobacterium avium subsp. paratuberculosis using Multiple-Locus Variable-number tandem-repeat Analysis:: first report in Argentina - Vasini Rosell, Brenda; Lagleyze, Bernardo; Morsella, Claudia; Mendez, Laura; Bresky, Florencia; Gioffré, Andrea; Paolicchi, Fernando (Brazilian Journal of Veterinary Research and Animal Science, 2020)
A pregnant heifer with an advanced clinical stage of paratuberculosis was reported in a herd in Argentina. Thus, the animal was euthanized and samples of organs of the cow and its fetus was taken and cultured for bacteriology in specific medium. Tissues were analyzed by histopathology (hematoxylin-eosin and Ziehl-Neelsen staining). Histopathological analysis of the cow’s samples revealed the presence of lesions consistent with paratuberculosis, and Ziehl-Neelsen staining revealed the presence of acid-fast bacilli, whereas the fetal tissues showed absence of lesions but the presence of acid-fast bacilli by Ziehl-Neelsen staining. After growing in specific medium, colonies in tissues from both cow and fetus were positive for IS900-PCR, confirming the presence of Mycobacterium avium subsp. paratuberculosis (MAP). Finally, the isolates were typed by Multiple-Locus Variable-number tandem-repeat Analysis (MLVA), which confirmedthe epidemiological link between them. This study is the first in Argentina to report the detection of MAP that shares an identical MLVA type in a pregnant cow and its fetus. The results of this study are consistent with previous reports and highlight the intra-uterine transmission of MAP as an important source of infection within herds.